Pengaruh Rasio Lancar, Rasio Hutang, Rasio Perputaran Aset Tetap, dan Rasio Pengembalian Atas Total Aset terhadap Probabilitas Kebangkrutan pada Perusahaan Manufaktur Sub Sektor Textil dan Garment yang terdaftar di Bursa Efek Indonesia Tahun 2011-2015 - Anna Adi Fitiati; Ridwan Singgih (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2016)
The purpose of this study is the effect of current ratio, debt ratio, fixed asset turnover ratio, and the ratio of return on total assets jointly to the probability of bankruptcy in the textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2011-2015. The data collection method used in this study is documentation. While the data analysis method used is the logistic regression analysis method, Assessing Fit Model (Simultaneous Test), Parameter Estimation and Interpretation, Nagelkerke R Square Analysis. From the results of logistic regression analysis it is known that the significance value of the current ratio variable (CR) is 0.225 which is greater than the value of a of 5% (0.225> 0.05) indicating that the current ratio variable (CR) has no significant effect on probability. The results of logistic regression analysis found that the significance value of the variable debt ratio (DER) is 0.118 which is greater than the value of a of 5% (0.118> 0.05) indicating that the variable debt ratio (DER) has no significant effect on probability. The results of logistic regression analysis found that the significance value of the fixed asset turnover ratio (TATO) variable is 0.256 which is greater than the value of a of 5% (0.256> 0.05) indicating that the fixed asset turnover ratio (TATO) variable does not have a significant effect on probability . The results of logistic regression analysis show that the significance value of the variable ratio of return on total assets (ROA) is equal to 0.003 which is smaller than the value of a of 5% (0.003 <0.05). This shows that the variable ratio of return on total assets (ROA) has a significant effect on probability. The results of the logistic regression analysis revealed the value of Chi-Square by using the Omnibus Test of 21.968 and a significance value of 0,000 <0,05 which means that there is a significant effect of current ratio, debt ratio, fixed asset turnover ratio, and the ratio of return on total assets jointly to the probability of bankruptcy in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange Year 2011-2015.